2016
DOI: 10.1177/1528083715613632
|View full text |Cite
|
Sign up to set email alerts
|

Seam properties of ultrasonic welded multilayered textile materials

Abstract: This study examined the effects of ultrasonic welding parameters on bond strength, seam thickness and seam stiffness, as well as water permeability. For study purpose, two types of four-layered fabrics with same compositions and different areal densities suitable for inner part of sport shoes were used. Two different types of seams, lapped and superimposed, were applied for ultrasonic welding and also compared by traditional seam applied by shoe manufacturer. The morphology of different type of seams was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Simona Jesvnik and et.al [9] conducted an experiment on Polyurethene to Polyamide using process parameters Frequency, Velocity and Pressure to influence effect on Bonding Strength and Weld Quality and analyzed experimental reading through Student T-Test. Statistical analysis showed that ultrasonic welding parameters, such as Velocity and welding frequency has high impact on the bending stiffness, thickness and bond strength of welded seams, but the obtained results were statistically insignificant.…”
Section: Litrature Reviewmentioning
confidence: 99%
“…Simona Jesvnik and et.al [9] conducted an experiment on Polyurethene to Polyamide using process parameters Frequency, Velocity and Pressure to influence effect on Bonding Strength and Weld Quality and analyzed experimental reading through Student T-Test. Statistical analysis showed that ultrasonic welding parameters, such as Velocity and welding frequency has high impact on the bending stiffness, thickness and bond strength of welded seams, but the obtained results were statistically insignificant.…”
Section: Litrature Reviewmentioning
confidence: 99%
“…The multilayer material with the integrated waterproof layer such as SympaTex ® or GoreTex ® are the most frequently used materials. The traditional joining technique used for joining the multilayer waterproof material for the inner socks of the shoes was carried out in two steps in order to keep the waterproofness [27]. The multilayered fabrics were sewn by zig-zag stitches with the predefined specifications.…”
Section: Seam Properties Of Hot Air Welded Multilayer Materialsmentioning
confidence: 99%
“…The waterproof tape has to be welded exactly on the middle (±1 mm) of the seam and during welding puckering of the membrane should be avoided. Next, the hot air welding was carried out at the following processing conditions: temperature of hot air was 365-380°C, the speed of welding was 2.5 m/min., the pressure of welding was 0.7 bar, the pressure between welding wheels was 2.5 bar, and the pressure of hot air blowing was 0.6 bar [27]. Table 4 presents the characteristics and visual appearance of a joining seam of a multilayered material for shoes.…”
Section: Seam Properties Of Hot Air Welded Multilayer Materialsmentioning
confidence: 99%
See 2 more Smart Citations